Travel to altitude with neurological disorders - Corrado Angelini; Guido Giardini; Marika Falla (University of Applied Sciences in Tarnow, Poland, 2021)
The present review examines several neurological conditions and the problems posed by travelling to high altitude, and in particular whether the underlying disease is likely to worsen. The neurological conditions include migraine and other types of headaches, transient ischemia of the brain, occlusive cerebral artery diseases, intracranial haemorrhage and vascular malformations, intracranial space occupying mass, multiple sclerosis, peripheral neuropathies, neuromuscular disorders, epileptic seizures, dementia and Parkinson's disease. Attempts will be made to classify the risk posed by each condition and to provide recommendations regarding medical evaluation, advice for or against travelling to altitude and effective prophylactic measures. Some individual cases should only be advised after careful examination and risk evaluation either in an outpatient mountain medicine service or by a physician with knowledge of travelling and high altitude risks. Recent developments in diagnostic methods and treatment of neurological conditions are also mentioned.